Validating the use of stereo‐video cameras to conduct remote measurements of sea turtles. Issue 12 (26th May 2021) - Siegfried, Tabitha R.; Fuentes, Mariana M. P. B.; Ware, Matthew; Robinson, Nathan J.; Roberto, Emma; Piacenza, Joseph R.; Piacenza, Susan E.
Abstract: Point 1: Stereo‐video camera systems (SVCSs) are a promising tool to remotely measure body size of wild animals without the need for animal handling. Here, we assessed the accuracy of SVCSs for measuring straight carapace length (SCL) of sea turtles. Point 2: To achieve this, we hand captured and measured 63 juvenile, subadult, and adult sea turtles across three species: greens, Chelonia mydas ( n  = 52); loggerheads, Caretta caretta ( n  = 8); and Kemp's ridley, Lepidochelys kempii ( n  = 3) in the waters off Eleuthera, The Bahamas and Crystal River, Florida, USA, between May and November 2019. Upon release, we filmed these individuals with the SVCS. We performed photogrammetric analysis to extract stereo SCL measurements (eSCL), which were then compared to the (manual) capture measurements (mSCL). Point 3: mSCL ranged from 25.9 to 89.2 cm, while eSCL ranged from 24.7 to 91.4 cm. Mean percent bias of eSCL ranged from −0.61% (±0.11 SE ) to −4.46% (±0.31 SE ) across all species and locations. We statistically analyzed potential drivers of measurement error, including distance of the turtle to the SVCS, turtle angle, image quality, turtle size, capture location, and species. Point 4: Using a linear mixed effects model, we found that the distance between the turtle and the SVCS was the primary factor influencing measurement error. Our research suggests that stereo‐video technology enables high‐quality measurements of sea turtle body size collected in situ without the need for hand‐capturing individuals. This study contributes to the growing knowledge base that SVCS are accurate for body size measurements independent of taxonomic clade. Abstract : Are stereo‐video cameras accurate for marine megafauna? This new study suggests that SVC are highly accurate for sea turtles (mean percent bias −0.76%–4.46% across species). Accuracy was influenced by distance between the SVC and the turtles, but not by angle, image quality, or animal size.